"Pyoderma gangrenosum of the breast: A challenging diagnosis". Issue 11 (25th July 2020) - Cabañas Weisz, Laura M.; Vicario Elorduy, Eduardo; García Gutiérrez, Juan José
Abstract: Pyoderma gangrenosum (PG) of the breast is a rare, ulcerative disease of rapid onset normally associated with systemic disorders and triggered by surgery or trauma. Pyoderma gangrenosum poses a diagnostic challenge. Early diagnosis and appropriate treatment are essential to minimize morbidity and sequelae. We performed a retrospective review of all breast PG cases admitted to Cruces University Hospital over a 5‐year (2015‐2019) period. Medical history, clinical course, and management strategies were assessed. Three patients were analyzed. None of them had previous surgery. No definitive etiology was identified in one case, and the other two were probably biopsy‐driven. Histological findings were reported as nonspecific. Similar skin lesions elsewhere on the body and resistance to wide‐spectrum antibiotic therapy were observed. These features raised awareness on the diagnosis of PG. Ulcerations healed completely within 2 months following treatment with Cyclosporine A or corticosteroid therapy. A complicated late‐diagnosis case that presented with advanced breast and forearm necrosis was managed with steroids followed by trans‐forearm amputation and mastectomy. The breast is an unusual site for PG, but this differential diagnosis should be considered in the presence of breast ulceration. In patients with a strong clinical and histological PG suspicion, we suggest early management with systemic corticosteroids and immunosuppressive therapy prior to any surgical debridement to minimize morbidity and poor esthetic outcomes.